Meningkatkan Aktivitas Dan Hasil Belajar Siswa Menggunakan Model PBL Dan TGT DI SDN Kelayan Banjarmasin - Harmina; Mahmuddin (CV. ITTC INDONESIA, 2023)
The low learning outcomes of students in science learning content so that researchers raise this problem, this is because learning has not developed problem-solving skills and scientific attitudes so that students have less potential to achieve comprehensive learning outcomes. Efforts to overcome these problems are by using a combination of Problem Based Learning learning models, Team Games Tournament and Concrete Objects Media animal life cycle materials. This study aims to describe educator activities, increase student activity and improve student learning outcomes. The approach used in this study is a qualitative research approach with the type of Classroom Action Research (PTK). The subject of this study was a grade 4 student of SDN Kelayan Dalam 7 Banjarmasin. Qualitative data are obtained from observations of teacher activity and student activity. The results of the study proved that educator activity increased and it can be concluded that with a combination of Problem Based Learning models, Team Games Tournament and Media concrete objects are able to optimize the activities of educators and students, it is recommended to use the model as an alternative in improving student learning outcomes.